Auditing and Optimization of Pueblo Vieio Gold Processing Plant - Deepak Malhotra (The Minerals, Metals and Materials Society, 1989)
Rosario Dominicana, S.A., operates a gold processing complex at Pueblo Viejo, northwest of Santo Domingo (Dominican Republic). The plant processes approximately 10,000 mtpd of oxide gold-bearing ore with a work index of 11 kWh/mt. The ore hardness has increased to about 17 kWh/mt. Metallurgical auditing of the plant was conducted? to find ways to modify the circuit to process hard ore without sacrificing throughput. In addition, unit operations were optimized to increase recovery and reduce operating cost,. The results of modifications made in the plant are discussed in this paper.